Experience of the use of anti-adhesive barrier based on sodium hyaluronate and carboxymethylcellulose in gynecological surgery - A. S. Molotkov; E. N. Popov; A. O. Ivanova; E. V. Kazantseva (Медицинский совет, 2019)
The article presents our experience in the use of anti-adhesive barrier based on hyaluronic acid and carboxymethylcellulose in gynecological surgery. The study included 63 patients who underwent removal of polyps, uterine fibroids, intrauterine synechiae, removal of ovarian cysts. At the end of operations an anti-adhesive gel was introduced into the uterine cavity and into the abdominal cavity to prevent adhesions. Efficacy and safety were assessed in the early postoperative period and with a further sixmonth follow-up of patients. It is noted that the introduction of the gel does not lead to the development of hyperthermic reactions, and in the postoperative period in patients there is no increase in the level of leukocytes (6.3 ± 0.2 x 109/L before the operation and 5.8 ± 0.5 x 109/L in postoperative period). In 89.7% of patients after surgical interventions, normalization of the menstrual cycle was noted, in 23% of patients with infertility, pregnancy was noted. When carrying out ultrasound of the pelvic organs and control hysteroscopy (in 7 cases), no evidence of the occurrence of adhesions was obtained.